(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Presents a wide range of content of the active substances of the bark and leaves of Salix and their multilateral use for pharmaceutical, cosmetic, and others.Among the many active ingredients, attention should be paid salicylic glycosides (salicin) and the different tannins (tannic acid, catechin), as well as resins, flavonoids and minerals. Due to the content of ac-tive substances for pharmaceutical purposes is used of Salix alba, Salix purpurea, S. capreaand S. fragilis.The ease of breeding species of Salixallows to obtain hybrids with in-creased levels of active substances, particularly valuable salicin. Depending on the kind of the active compound isolated from the bark or leaves of willow, isimportantthe age of the plant material and the time of obtaining the raw material